Advanced Nanomaterials for the Diagnosis and Treatment of Renal Cell Carcinoma. Issue 2 (7th February 2023) - Ji, Chen; Li, Junru; Mei, Junyang; Su, Weiran; Dai, Huili; Li, Fengqin; Liu, Peifeng
Abstract : Nanomaterials Renal cell carcinoma (RCC) is the most common type of kidney cancer and has a high morbidity rate, which requires robust materials for diagnosis and treatment. In article number 2200079, Huili Dai, Fengqin Li, Peifeng Liu, and co‐workers review the applications of various nanomaterials including lipid, inorganic, natural, and synthetic polymer nanomaterials in the diagnosis and therapy of RCC and highlight their respective advantages.